The Earnings Characteristics of Firms Reporting Discretionary Accounting Changes. - Bremser, Wayne G. (The Accounting Review, 1975)
Abstract This article presents a comparative analysis of the earnings characteristics of firms electing to make an accounting change and a similar group of firms not electing to make a change during the same period. The manipulative aspect of alternative methods of accounting for the same events has received significant attention in recent years. The apparent increasing frequency of reported accounting changes, or switching methods, has raised the question of potential abuses by company managements of the opportunity to switch to alternative accounting methods. In the present study, the reported earnings of a sample of 80 companies electing to make accounting changes in a year are contrasted with those of 80 companies not disclosing any accounting changes during the period. A dual analysis is presented. First, the pattern or trend of the companies' earnings per share is examined. The second approach is to compare the magnitude of the reported return on common stockholders' investment of the firms in the two groups.